2010
DOI: 10.1186/1471-2180-10-102
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to and biofilm formation on IB3-1 bronchial cells by Stenotrophomonas maltophilia isolates from cystic fibrosis patients

Abstract: BackgroundStenotrophomonas maltophilia has recently gained considerable attention as an important emerging pathogen in cystic fibrosis (CF) patients. However, the role of this microorganism in the pathophysiology of CF lung disease remains largely unexplored. In the present study for the first time we assessed the ability of S. maltophilia CF isolates to adhere to and form biofilm in experimental infection experiments using the CF-derived bronchial epithelial IB3-1cell line. The role of flagella on the adhesiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 43 publications
3
99
1
4
Order By: Relevance
“…S. maltophilia is an emerging, multidrug-resistant organism often associated with chronic lung infections, especially in cystic fibrosis patients. Of particular note, the prevalence of biofilm-producing S. maltophilia strains isolated from the lungs of cystic fibrosis patients and from contaminated medical equipment has implicated biofilm formation as a mechanism contributing to S. maltophilia infection and multidrug resistance (18). We find that Smlt1473 is secreted when overexpressed in Escherichia coli, and secretion depends on a predicted lipoprotein secretion signal sequence.…”
mentioning
confidence: 76%
“…S. maltophilia is an emerging, multidrug-resistant organism often associated with chronic lung infections, especially in cystic fibrosis patients. Of particular note, the prevalence of biofilm-producing S. maltophilia strains isolated from the lungs of cystic fibrosis patients and from contaminated medical equipment has implicated biofilm formation as a mechanism contributing to S. maltophilia infection and multidrug resistance (18). We find that Smlt1473 is secreted when overexpressed in Escherichia coli, and secretion depends on a predicted lipoprotein secretion signal sequence.…”
mentioning
confidence: 76%
“…Mutants of strain K279a were constructed using the gene replacement vector pEX18Tc as described previously (21,24,25). A mutant (NUS5) with a deletion of the entire stmPr1 coding region (SMLT_RS03270) was obtained using PCR overlap extension protocol as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…maltophilia can form biofilms on lung cells (73,83,268). Confocal microscopy of biofilms formed by CF isolate S. maltophilia OBGTC9 on CF sputum-derived bronchial epithelial IB3-1 cell monolayers revealed that S. maltophilia formed microcolonies embedded in a matrix (268).…”
Section: Molecular Mechanisms Involved In Pathogenesis Biofilmsmentioning
confidence: 99%
“…A significant feature of S. maltophilia is its ability to form biofilms on surfaces including Teflon, glass, and plastics and on host tissues (83,84,166,268). Biofilms have been estimated to be associated with 65% of hospital-acquired infections (270).…”
Section: Molecular Mechanisms Involved In Pathogenesis Biofilmsmentioning
confidence: 99%